Effect of Propylene Glycol and Laterite on California Bearing Ratio of Clay Shale - Nusyura Al Islami, Auliya; Rahayu, Wiwik; Susilo Soepandji, Budi (International Journal of Engineering and Technology, 2018)
Clay shale in natural condition has a very high strength. But due to weathering caused by exposure with air and water, its strength decreased significantly. Propylene glycol is established as an effective shale inhibitor in water-based muds. The effect mixing propylene glycol with clay shale to its strength is needs to be discussed. Sample of Citereup clay shale has been mixed with propylene glycol with ratio 0.3, 0.5, and 0.7 of its optimum water content. California Bearing Ratio test have been performed to determine clay shale bearing strength. Result from study indicate that clay shale stabilization using 30% propylene glycol can increase strength in unsoaked condition. Laterite soil mix were also give additional bearing strength to clay shale specimen.Â